Improving the Time to Antibiotic Administration in Paediatric Febrile Neutropenia: Implementation of a Clinical Care Pathway in Saudi Arabia - Pole, Maddi (Auckland University of Technology, 2021)
Febrile neutropenia is a commonly experienced condition in patients undergoing chemotherapy treatment or immunosuppressive therapies. Most chemotherapy patients will experience febrile neutropenia at least once in their treatment course. Febrile neutropenic infections develop and spread faster in those with inadequate immunity. In the paediatric population, timeliness and effective antibiotic treatment is paramount to avoiding long term organ damage, and septic related deaths. Best evidence suggests that antibiotic treatment, intravenous fluid resuscitation and blood test investigations should be completed within an hour of arrival to an emergency department for febrile neutropenic patients. This time frame is crucial in the prevention of potential organ damage, which can occur with as little as 3 hours of uncontrolled and untreated febrile neutropenia. Saudi Arabia had an average time to antibiotic administration of 3 hours and 48 minutes. The aim of this project was to develop and implement a clinical care pathway to guide health care professionals to adequately treat febrile neutropenia in the paediatric population in Saudi Arabia. Through a synthesis of current evidence, international best care practice and local guidelines, a pathway was developed. This pathway was implemented and reviewed in accordance with Rosswurm and Larrabee’s (1999) 6-step model for change to evidence practice, and the success and results of this project initiative are described in full below.
Keywords: Febrile neutropenia; Paediatric; Oncology; Emergency department; Clinical care pathway